ANALISIS WAKTU TUNGGU PELAYANAN RESEP PASIEN RAWAT JALAN DI DEPO FARMASI GEDUNG MCEB RS ISLAM SULTAN AGUNG SEMARANG - Nurma Katrinnada Purwandari; Antono Suryoputro; Septo Pawelas Arso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The outpatients at Sultan Agung Islamic Hospital complained about the long waiting time duration of their prescription services. This case primarily occured in the pharmaceutical depot at MCEB Bulding, a building which contained most of the specialist polyclinic. Thus at the rush hour causing the waiting time become longer. There are few things that considered to be the main cause of this long waiting periods, such as the lack of employee, the space of the room, the hospital information system and management (SIM RS), and also the still existence of prescribing that is not based on the formularium, that caused the waiting time service has not meet the standard, both the standard of minimum service standard (SPM) and hospital quality indicators (IMRS). The purpose of this study is to describe and identify the factors that lead to long periods of waiting times in prescription services, whichever on the general, national health insurance (JKN), and private health insurance patients. This research is a quantitative and qualitative research. The data of this research were collected with an observation sheet of the waiting time and with an in-depth interviews. The result of this research indicating that the average waiting time for non concoction prescription services is 48.9 minutes and concoction recipes is 46.54 minutes, whereas delay time in the process of non concoction recipes is 40.39 minutes which is larger than the action time 8.47 minutes. Recipe that do not reach waiting time standard mostly are the recipes for non concoction, mainly from JKN patients with percentage 85.7% on SPM standard and 57.1% on IMRS standard. The factors that lead this longer waiting period are the lacking numbers of employee, the SIM RS and the space of the room that has not been optimal, the big numbers of recipes that not suitable with the formulary, and the lack of understanding about standard operating procedure (SPO) and the waiting time standard. The few suggestion for this case are increasing the number of employees accompanied with expansing of the room’s space, maintaining the facility periodically, repairing SIM RS, and promoting about SPO and the waiting time standard.